Development of the Hand - B Baykal; S Turkkan (Journal of Embryology, 2017)
Development of the hand occurs as a complex series of events. In order to understand the mechanisms of developmental hand anomalies, the clinician has to understand the normal embryonic development of the hand. In this review, we present the development of the hand in the light of new literature knowledge.
Keywords: Development hand anomalies